Perceptions Of Threat Risk Frequency And Impact On Construction Projects In Ghana: Opinion Survey Findings - Chileshe, Nicholas; Fianko, Adwoa Boadua Yirenkyi (Penerbit Universiti Sains Malaysia, 2011)
Threat risks are experienced by all stakeholders in a construction project. Although the nature of these risks is understood, less is known about their likelihood of occurrence and potential impact. This study explored these elements of risk by using an opinion survey approach to collect data from 103 professionals (clients, consultants and contractors) in the Ghanaian construction industry. Signifcant differences were found between the perceptions of these sub-groups regarding the likelihood of occurrence of threat risks in fve categories: construction method; price inﬂation; exceptional weather; ground conditions and site contamination; and poor communication among the project team. The contractors rated ‘construction methods’ higher than did the clients, and they also rated ‘exceptional weather’ higher than either the clients or the consultants. On the other hand, consultants rated ‘price inﬂation’ higher than the clients. Signifcant differences between the sub-groups were also found regarding the potential impact of the threat risk of price ﬂuctuation. The consultants rated the ‘price ﬂuctuation’ threat risk higher than either the contractors or the clients. These fndings suggest that despite the existence of remedial strategies to protect some of the stakeholders from these risks, there is a fear of being blacklisted, thus compromising future opportunities (especially among contractors) should legal action be taken to redress the identifed problems (such as such delayed payments). The following implications are drawn: One of the suggested recourses is the introduction of bespoke rather than standard contracts, as these might introduce contract ﬂaws and contribute towards helping the project stakeholders monitor these potential risks and take appropriate action.